2016
DOI: 10.1016/s1473-3099(16)00072-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for active tuberculosis in migrants screened before entry to the UK: a population-based cross-sectional study

Abstract: Wellcome Trust, Medical Research Council, and UK National Institute for Health Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 24 publications
(34 reference statements)
3
46
1
3
Order By: Relevance
“…Between 2012 and 2015, the prevalence of active TB among contacts of ETB index cases in London was 0.7%,14 compared with 0.027% in the general population 15. Similar patterns are observed in Birmingham,16 17 and in both cities, the prevalence of disease among contacts of ETB cases was higher than the prevalence of disease among migrants eligible for pre-entry screening18 and more than 10 times higher than the NICE threshold for new entrant screening 17. Additionally, studies have shown only 25% of pairs of cases sharing an address in the UK,19 and 20% of case-contact pairs in London20 had different Mycobacterium tuberculosis isolates, implying the risk of disease in household contacts is high irrespective of whether transmission has occurred.…”
Section: Introductionmentioning
confidence: 53%
“…Between 2012 and 2015, the prevalence of active TB among contacts of ETB index cases in London was 0.7%,14 compared with 0.027% in the general population 15. Similar patterns are observed in Birmingham,16 17 and in both cities, the prevalence of disease among contacts of ETB cases was higher than the prevalence of disease among migrants eligible for pre-entry screening18 and more than 10 times higher than the NICE threshold for new entrant screening 17. Additionally, studies have shown only 25% of pairs of cases sharing an address in the UK,19 and 20% of case-contact pairs in London20 had different Mycobacterium tuberculosis isolates, implying the risk of disease in household contacts is high irrespective of whether transmission has occurred.…”
Section: Introductionmentioning
confidence: 53%
“…Radiology could also have an important role in the diagnosis of TB in low-resource countries, especially as pre-entry TB screening in country of origin for those migrants who intend to migrate and refugees. However, the equipment is expensive and it needs qualified and experienced staff to be able to interpret the radiological signs-they are not always available in these settings [23,45,56,57]. Moreover, CXR cannot provide a conclusive diagnosis on its own and needs to be followed by sputum testing.…”
Section: Conventional Diagnostic Methodsmentioning
confidence: 99%
“…Moreover, programs differ by whether screening is done for active TB or LTBI, or both. The programs also differ in relation to arrival in the host country, i.e., the migrants' status, such as refugees or asylum seekers, the countries of origin, and tools used to screen for active TB or LTBI [22,23]. The rationale of these programs is the early detection and treatment of active and often contagious TB cases in order to prevent Mycobacterium tuberculosis transmission to the host population of a low-burden country and reduce the burden of imported TB in low-incidence countries.…”
Section: Screening Practices Among Adultsmentioning
confidence: 99%
“…Considering the key symptoms of TB (fever, cough of at least 2 weeks' duration, weight loss, night sweats), the majority of individuals at risk can be identified and should be referred to a hospital for assessment and early treatment initiation. In a population-based cross-sectional study, Aldridge et al [29] screened 476,455 visa applicants in the UK for TB, and migrants reporting contact with an individual with TB had the highest risk of TB at pre-entry screening. As a consequence, the authors call for a comprehensive and collaborative approach between countries with preentry screening programs as well as health services in the countries of origin and migration to tackle the disease [29].…”
Section: Health Problems In Refugee Camps and Other Reception Sitesmentioning
confidence: 99%